An investigation of bamboo-strips constructions built according to Yona Friedman's manuals. Issue 1 (25th February 2019) - Chiacchiera, Paolo; Bocco, Andrea; Ceretto, Walter; Ghirardotti, Davide
Abstract : This paper describes a research on structural and constructional properties of bamboo strips, used in accordance with some manuals to improve the quality of self-building, which were authored by Yona Friedman. To investigate these properties, four full-scale roof structures of different design have been built and tested to find their maximum load, deformation behaviour and failure. Two of these have been subsequently rebuilt to explore strengthening possibilities that were assessed through further tests, which showed an increase of maximum load. Besides field tests, the bamboo roofs were modelled making use of a finite elements analysis software, in order to evaluate the correspondence between experimental and analytical data. The results show remarkable differences between the actual behaviour of the structures and that obtained from the modelling, due among other things to the dimensional unevenness of strips and the imperfect execution of lashed joints: the latter not always allowed to obtain that ideal hinge bearing condition, that had been hypothesised in the analytical model.